Could toll-like receptors provide a missing link in chronic inflammation in rheumatoid arthritis? Lessons from a study on human rheumatoid tissue. (12th October 2007) - Sacre, Sandra M; Drexler, Stefan K; Andreakos, Evangelos; Feldmann, Marc; Brennan, Fionula M; Foxwell, Brian M J
Abstract : In the last decade the development of a number of biological therapies has revolutionised the treatment of rheumatic diseases. The first and most widely used of these approaches, tumour necrosis factor (TNF) blockade (infliximab, entanercept, adalimumab), has now been administered to over a million patients. However, the success of these biological therapies has also highlighted their limitations. None of these treatments has shown a 100% patient response; normally responses are in the 50–70% range. As proteins, these drugs cannot be given orally and they are expensive to produce, a cost ultimately borne by the patient/health provider that can seriously limit the availability of these drugs. Lastly, these treatments, whether involving the systemic neutralisation of a cytokine (eg, TNF or IL6 receptor blockade (tocilizumab)), the ablation of a B cell population (anti-CD20, rituximab), or the potential disruption of important cellular interactions as with CTLA4-Ig (abatacept), can cause major perturbations of the immune system, the long-term effects of which are still unclear. At present, treatments such as TNF blockade can result in an increased infectious risk and the reactivation of tuberculosis can be a major issue in certain populations. As with all therapies, there is an increasing large refractory population over time. Therefore, despite the undoubted success of these therapies, there is room for improvement. Although it might be too much to expect any new treatment to affect a "cure" (all the current biological therapies require repeated administrations), there are definite gains to be made in terms of cost, oral bioavailability and a more selective interference with the immune–inflammatory response.